Population‐based study of the impact of small bowel obstruction due to adhesions on short‐ and medium‐term mortality. Issue 13 (9th August 2019) - Behman, R.; Nathens, A. B.; Haas, B.; Look Hong, N.; Pechlivanoglou, P.; Karanicolas, P.
Abstract : Background: Small bowel obstruction due to adhesions (aSBO) is a common indication for admission to a surgical unit. Despite the prevalence of this condition, the short‐ and medium‐term survival of this patient population has not been well described. The purpose of this study was to measure the short‐ and medium‐term survival of patients admitted to hospital with aSBO. Methods: Linked administrative data were used to identify patients admitted to hospital in Ontario, Canada, for aSBO between 2005 and 2011. Patients were divided into two groups: those aged less than 65 years (younger group) and those aged 65 years and older (older group). Thirty‐day, 90‐day and 1‐year mortality rates were estimated. One‐year mortality was compared with that in the general population, adjusting for age and sex. The timing of deaths in relation to admission was assessed, as well as the proportion of patients discharged before experiencing short‐term mortality. Results: There were 22 197 patients admitted to hospital for aSBO for the first time in the study interval. Mean age was 64·5 years and 52·2 per cent of the patients were women. Overall, the 30‐day, 90‐day and 1‐year mortality rates for the cohort were 5·7 (95 per cent c.i. 5·4 to 6·0), 8·7 (8·3 to 9·0) and 13·9 (13·4 to 14·3) per cent respectively. For both groups, the 1‐year risk of death was significantly greater than that of the age‐matched general population. The majority of deaths (62·5 per cent) occurred within 90 days of admission, with 36·4 per cent occurring after discharge from the aSBO admission. Conclusion: Patients admitted with aSBO have a high short‐term mortality rate. Increased monitoring of patients in the early period after admission is advisable. Abstract : The risk of 30‐day, 90‐day and 1‐year mortality is extremely high among patients admitted for adhesive small bowel obstruction. Moreover, more than one‐third of deaths occur after discharge from hospital but within 90 days of the initial small bowel obstruction admission, suggesting that more careful monitoring of patients in this early period after admission may be critical. Higher than expected. Abstract : Antecedentes: La obstrucción del intestino delgado por adherencias ( adhesive small bowel obstruction, aSBO) es una indicación frecuente de ingreso en una unidad quirúrgica. A pesar de la prevalencia de esta patología, la supervivencia de estos pacientes a corto y a medio plazo no ha sido bien descrita. El objetivo de este estudio fue determinar la supervivencia a corto y a medio plazo de pacientes con aSBO ingresados en el hospital. Métodos: Utilizando el enlace de datos administrativos se identificaron a los pacientes ingresados por aSBO en Ontario, Canadá, entre 2005‐2011. Los pacientes se dividieron en dos subgrupos: los menores de 65 años de edad (subgrupo joven) y los de 65 años o más (subgrupo mayor). Se estimó la mortalidad a los 30 días, 90 días y a 1 año. La mortalidad a 1 año se comparó con la de la población general, ajustando por edad y sexo. Se evaluó el momento del fallecimiento respecto al ingreso, así como la proporción de pacientes que fueron dados de alta antes de fallecer a los 30 días. Resultados: Durante el periodo de estudio se ingresaron en el hospital 22.197 pacientes con aSBO por primera vez. La edad media de los pacientes era de 65 años y un 52% eran mujeres. La mortalidad global de la cohorte a los 30 días, a los 90 días y a 1 año fue del 5, 7% (i.c. del 95%: 5, 4‐6, 0%), 8, 3% (i.c. del 95%: 8, 3‐9, 0%) y 13% (i.c. del 95%: 12, 9‐15, 0%), respectivamente. Para ambos subgrupos, el riesgo de mortalidad a 1 año fue significativamente mayor que en la población general emparejada por edad. La mayoría de los fallecimientos (59%) ocurrieron durante los 90 días del ingreso, con un 36% tras el alta después del ingreso por aSBO. Conclusión: Los pacientes ingresados por aSBO presentan una alta mortalidad a corto plazo. Se recomienda incrementar la vigilancia de estos pacientes en el periodo temprano tras el alta hospitalaria.